Explicit and Implicit Structuring of Genres in Electronic Communication: Reinforcement and Change of Social Interaction - Yates, JoAnne; Orlikowski, Wanda J.; Okamura, Kazuo (Organization Science, 1999)
In a study of how an R&D group in a Japanese firm adopted and used a new electronic medium, we identified two contrasting patterns of use: the use of community-wide communication types, or genres, deliberately shaped by the action of a small, sanctioned group of mediators; and the use of local genres tacitly shaped by members within their own research teams. We suggest that these patterns reflect the more general processes of explicit and implicit structuring, resulting in both the reinforcement and change of social interaction within communities. Explicit structuring included the planned replication, planned modification, and opportunistic modification of existing genres, while implicit structuring included the migration and variation of existing genres. We believe that these two processes provide suggestive models for understanding the initial and ongoing use of new electronic media within a community.